(untitled) (Journal of the College of Basic Education, 2022)
The tremendous development in the information and communication technology system in the world has greatly affected the life, social, economic, political and cultural aspects in general, and the educational one in particular, as it has a major role in running a lot of things.And that the contribution of information systems and computers to the development of science, research and development, industry affairs and governance has become known and recognized at all levels, and some of them believe that the progress made in the field of electronics and information technology has brought about a cultural revolution that is comparable to the revolution in the emergence of writing, and it is likely that political changes will occur in the future and in The content of science courses and arenas in information and communication technology. (Raphael, 1985, p. 36)